Impact of farm management practices and agricultural land use on soil organic carbon storage potential in the Savannah Ecological zone of Northern Ghana - Boakye-Danquah, J.; Antwi, E.K.; Saito, O.; Abekoe, M.K.; Takeuchi, K. (Journal of Disaster Research, 2014)
In recent times, there has been increasing interest in the importance of agricultural soils as global carbon sinks, and the opportunity of enhancing the resilience of degraded agroecosystems - particularly in savannah regions of the world. However, this opportunity is largely a function of land use and/or land management choices, which differ between and within regions. In the present study, we investigated the role of agriculture land use and farm management practices on soil organic carbon (SOC) storage in the savannah regions of northern Ghana. We evaluated selected land use types by using an integrated approach, involving on-farm interviews, community transect walks, land use monitoring, and soil sampling. Our results indicated that, at the landscape level, community land use and resource needs are important determinants of SOC storage in farmlands. We determined low SOC accumulation across the investigated landscape; however, the relatively high SOC stock in protected lands compared with croplands implies the potential for increasing SOC build-up by using recommended management practices. Low incomes, constraints to fertilizer use, low biomass availability, and reductions in fallow periods remain as barriers to SOC buildup. In this context, global soil carbon storage potential and smallholder food production systems will benefit from an ecosystembased adaptation strategy that prioritizes building a portfolio of carbon stores at the landscape level.
Keywords: Agricultural land use; Farm management practices; Northern ghana; Soil organic carbon